Mathematical foundations of computer science 2015. 40th International Symposium, MFCS 2015, Milan, Italy, August 24-28, 2015, Proceedings /: 40th International Symposium, MFCS 2015, Milan, Italy, August 24-28, 2015, Proceedings. Part II : (2015) - Unknown
No abstract available